Aquaculture Database System for Culture Practices - Mahalakshmi, P.; Panigrahi, A.; Ghoshal, T. K.; Biswas, G.; Ananda Raja, R.; Kumar, Sujeet (Fishery Technology, 2018)
Aquaculture Database System was developed for the management of information on aquaculture practices collected by the research institutes and other organizations using Integrated Development Environment of software. In this system, 29 tables and their corresponding relationships were designed by one-to-one mapping cardinality. The main screen was designed into four modules namely, Entry, Search, User Manual and Exit. The entry module allows the user to add culture practices information into their corresponding table for storing. The search module allows the user to retrieve the required information from their corresponding tables. The results can be displayed in the report format and also it can be exported to MSWord or MSExcel. In addition, the basic statistical analyses like frequency, percentage, mean and standard deviation was designed in the output screen based on their requirements. The system has been tested using the farm data collected from the brackishwater aquaculture area in West Bengal. Although illustrations are based on the brackishwater, ADS is general and can act as a model to capture and analyze the data for all other aquaculture practices.